Taxation, Innovation and Entrepreneurship - Ulrich Schetter; Hans Gersbach; Maik Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We examine how basic research should be financed. While basic research is a public good benefiting innovating entrepreneurs it also affects the entire economy: occupational choices of potential entrepreneurs, wages of workers, dividends to shareholders, and aggregate output. We show that the general economy impact of basic research rationalizes a pecking order of taxation to finance basic research. In particular, in a society with desirable dense entrepreneurial activity, a large share of funds for basic research should be financed by labor taxation and a minor share is left to profit taxation. Such tax schemes induce a significant share of agents to become entrepreneurs, thereby rationalizing substantial investments in basic research. These entrepreneurial economies, however, may make a majority of citizens worse off if those individuals do not possess shares of final good producers in the economy. In such circumstances, stagnation may prevail.
Keywords: H20; H40; O38; 330